Math, asked by angeltreesa012, 3 months ago

please help me with this fast​

Attachments:

Answers

Answered by senboni123456
2

Step-by-step explanation:

We have,

 \rm \: x =   \frac{ \sqrt{3}  -  \sqrt{2} }{ \sqrt{3} +  \sqrt{2}  } \\  y =  \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3} -  \sqrt{2}  }

Now,

 \rm \:  {x}^{2}  +  {y}^{2} + xy

 \rm \:  =  {x}^{2}  +  {y}^{2} + 2xy  - xy

 \rm \:  =  {(x + y)}^{2}    - xy

 \rm \:  =  { \bigg( \frac{ \sqrt{3} -  \sqrt{2}  }{ \sqrt{3}  +  \sqrt{2} }   +  \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3} -  \sqrt{2}  } \bigg)}^{2}    -  \bigg( \frac{ \sqrt{3} -  \sqrt{2}  }{ \sqrt{3}  +  \sqrt{2} }  \bigg). \bigg( \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3}  -  \sqrt{2} }  \bigg) \\

 \rm \:  =  { \bigg \{ \frac{ (\sqrt{3} -  \sqrt{2} ) ^{2} + (\sqrt{3}  +   \sqrt{2} ) ^{2} }{( \sqrt{3}  +  \sqrt{2})( \sqrt{3}  -  \sqrt{2})  }  \bigg \}}^{2}    -  1 \\

 \rm \:  =  { \bigg \{ \frac{ 2 \{(\sqrt{3} )^{2}  +  (\sqrt{2} ) ^{2}  \} }{(\sqrt{3})^{2}  -  (\sqrt{2})^{2}   }  \bigg \}}^{2}    -  1 \\

 \rm \:  =  { \bigg \{ \frac{ 2 \{3 +  2  \} }{3  - 2  }  \bigg \}}^{2}    -  1 \\

 \rm \:  =  { \bigg \{ \frac {2 \times 5 }{1}  \bigg \}}^{2}    -  1 \\

 \rm \:  =  (10)^{2}   -  1 \\

 \rm \:  =  100   -  1  = 99\\

Similar questions